PENERAPAN MODEL POPULASI KONTINU PADA PERHITUNGAN PROYEKSI PENDUDUK (STUDI KASUSDI KECAMATAN SINONSAYANG) - Mangobi, James; Salajang, Santje; Goguyu, Irfan (LPPM Politeknik Saint Paul Sorong, 2024)
Population projections are scientific estimates based on assumptions about the factors that contribute to population growth rates, such as migration, births, and deaths. They are not population predictions. The future population's size and age distribution are determined by these three factors. Data describing trends from the past to the present are needed to make estimates about the pace of development of future births, deaths, and movements. The goal of this study is to use the logistic and exponential growth models to project the population growth in Sinonsayang Subdistrict. BPS Sinonsayang Subdistrict provided the population census data for Sinonsayang Subdistrict from 2016 to 2022. Both logistic and exponential models are used to model data analysis procedures. The model that was chosen was based on the findings.